Nivel de conocimientos de los estudiantes del Colegio Nacional San Pedro de Vilcabamba del cantón Loja; sobre las consecuencias que conlleva el inicio precoz de la vida sexual y la práctica de una sexualidad no responsable. - Jiménez Paute, Beatriz Elizabeth (2013)
The present study aims to identify the level of knowledge possessed by college students " National San Pedro de Vilcabamba." about the consequences that entails the onset of precocious sexuality, the same that is descriptive, transversal, for which it had 80 students from 13-17 years of age, who met the inclusion and exclusion criteria, to which we applied a survey as a means of data collection, prior to the authorization provided by facility authorities and parents of family. It was noticed that only 20 % of teens surveyed have already started your sexual life, 15 years being the most common age of onset, 70 % report having little information about sexuality. This will take appropriate measures such as the provision of knowledge, through the implementation of sex education programs and prevention of the consequences, to assist teens in making appropriate decisions, to enjoy a healthy sex life, successful and responsible. Keywords: Sexuality precocious, adolescents, National College San Pedro de Vilcabamba.